2023
DOI: 10.3390/su15107906
|View full text |Cite
|
Sign up to set email alerts
|

Transport/Detachment Regimes of Different Size Class Sediment Particles and Enlightenments for Transport Capacity Prediction for Rain-Induced Overland Flow Erosion

Abstract: The transport/detachment regimes of each particle size vary with size. Moreover, the changing transport/detachment regimes of sediments with size and their related mechanisms considerably affect sediment transport capacity (Tc). To investigate the transport/detachment regimes of each particle size and their explanation for Tc prediction, 27 simulated rainfall experiments were conducted under slope gradients of 8.7%, 17.6%, and 26.7% and rainfall intensities of 60, 90, and 120 mm h−1. The experimental soil was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Inter ow makes a non-negligible contribution to the horizontal migration of HMs 43 , and the release of HMs from inter ow stems from interactions between the soil liquid-phase and solid-phase matrices, including processes such as adsorption/desorption and dissolution/precipitation, as well as the complexation of ions in soil 2 . Some previous studies 44 have shown that the mobility of solutes in surface runoff increases as the slope increases, and this promotes the dilution and transport of HMs in runoff. The inter ow yield was highest in the S5 treatment at slower ow rates.…”
Section: Discussionmentioning
confidence: 89%
“…Inter ow makes a non-negligible contribution to the horizontal migration of HMs 43 , and the release of HMs from inter ow stems from interactions between the soil liquid-phase and solid-phase matrices, including processes such as adsorption/desorption and dissolution/precipitation, as well as the complexation of ions in soil 2 . Some previous studies 44 have shown that the mobility of solutes in surface runoff increases as the slope increases, and this promotes the dilution and transport of HMs in runoff. The inter ow yield was highest in the S5 treatment at slower ow rates.…”
Section: Discussionmentioning
confidence: 89%